Integrating government policy and facility-based interventions in improving E-waste recycling: Incentives as a moderator of sustainability impact - Beleya, Prashanth; Airawaty, Diana; Krishna, Tanaraj; Veerappan, Geetha; Salehi, Sadegh (International Journal of Innovative Research and Scientific Studies, 2025)
Electronic waste (e-waste) is the fastest-growing waste stream globally, producing over 53.6 million metric tons in 2022 and projected to increase to 74 million tons by 2030. Unfortunately, only 17% of worldwide e-waste is collected and recycled properly, resulting in millions of tons of improperly discarded items that can significantly harm the environment. This issue is also prevalent in Malaysia, which generates an estimated 280,000–365,000 tons of e-waste annually, with low recycling rates among households. This study investigates the factors contributing to low household e-waste recycling in Malaysia. Three factors were assessed through a quantitative survey of 384 urban households in Ipoh, a northern Malaysian state. Facilities and government policy were identified as independent variables, while incentives served as a moderating variable to enhance household recycling. The findings suggest that incentives influence government policy, whereas facilities are unaffected by incentives in promoting recycling. As e-waste volumes grow, Malaysian households have largely resisted integrating e-waste recycling into their daily routines, often discarding gadgets improperly or selectively. The researchers emphasize the urgent need for comprehensive strategies, including increased consumer awareness, accessible take-back programs, incentive schemes, and stricter policies to improve e-waste recycling and sustainability. The study offers integrated recommendations for policymakers and stakeholders to enhance recycling practices and highlights areas for future research in sustainable waste management.